2018
DOI: 10.1186/s40510-018-0240-2
|View full text |Cite
|
Sign up to set email alerts
|

Zygomaticomaxillary modifications in the horizontal plane induced by micro-implant-supported skeletal expander, analyzed with CBCT images

Abstract: BackgroundMiniscrew-assisted rapid palatal expansion (MARPE) has been adopted in recent years to expand the maxilla in late adolescence and adult patients. Maxillary Skeletal Expander (MSE) is a device that exploits the principles of skeletal anchorage to transmit the expansion force directly to the maxillary bony structures and is characterized by the miniscrews’ engagement of the palatal and nasal cortical bone layers. In the literature, it has been reported that the zygomatic buttress is a major constraint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 31 publications
1
27
0
2
Order By: Relevance
“…In the protocol developed, the center of MSE appliance and hence the expansion force vector is set by default in the same position as the CM point, defined by the projection of the bizygomatic line (BZL) on the posterior part of the midpalatal suture. In the literature, it has been described that the pterygopalatine suture 28,29 and the zygomatic buttress bone [23][24][25][26]30,31 are two major resistance structures that hamper the lateral maxillary movement. Furthermore, Lee et al 32 have shown that the center of resistance of the maxillary halves is located slightly superiorly and laterally to the root apex of maxillary second molars, close to the most lateral point of the zygomatic process of the maxilla (ZR and ZL) utilized in our protocol.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the protocol developed, the center of MSE appliance and hence the expansion force vector is set by default in the same position as the CM point, defined by the projection of the bizygomatic line (BZL) on the posterior part of the midpalatal suture. In the literature, it has been described that the pterygopalatine suture 28,29 and the zygomatic buttress bone [23][24][25][26]30,31 are two major resistance structures that hamper the lateral maxillary movement. Furthermore, Lee et al 32 have shown that the center of resistance of the maxillary halves is located slightly superiorly and laterally to the root apex of maxillary second molars, close to the most lateral point of the zygomatic process of the maxilla (ZR and ZL) utilized in our protocol.…”
Section: Discussionmentioning
confidence: 99%
“…The application of the expansion force vector close to the maxillary center of resistance has the scope of maximizing the orthopedic effect on the midface during maxillary expansion. [23][24][25][26] If the CA is moved forward relative to the CM point, the midpalatal suture opening will be less parallel and more V-shaped, since the force vector will act in a more anterior part of the maxilla, away from its center of resistance. 32 Although MSE position relative to the bizygomatic line and CM point is the main objective of the digital planning due to biomechanical reasons, other parameters were taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The maxilla is located medially and anteriorly relative to this fulcrum. Due to the outward rotation of the zygomaticomaxillary complex around the proximal part of the zygomatic process, each half of the maxilla will be displaced forward and laterally [36]. Additionally, the asymmetrical lateral movement of the cheek points and the alar curvature points between the left and right side could be explained by the unequal movement of the two maxillary bones.…”
Section: Discussionmentioning
confidence: 99%